MENANAMKAN NILAI MORAL PADA PESERTA DIDIK MELALUI PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Muhammad Toto Nugroho (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to find out what methods can be applied by teachers to instill moral values in elementary school students through Islamic religious education. The method used in this research is descriptive qualitative method. Data collection techniques using interviews, observation and documentation. The data analysis technique in this study adopted the Miles and Hubberman model starting from data collection, data reduction, data presentation and drawing conclusions. The results of the study are to instill moral values to students through learning Islamic religious education, using several learning methods. The method used is in the form of storytelling, demonstration, assignment and habituation methods, the application of these methods must be applied continuously. This research can be one of the considerations for teachers to instill moral values to students through Islamic religious education, where this moral value is very important for every student at the elementary school level. Keywords: Moral Values, Elementary School Students, Islamic Religious Education.